2000
DOI: 10.1063/1.1333403
|View full text |Cite
|
Sign up to set email alerts
|

Detection of up to 20 THz with a low-temperature-grown GaAs photoconductive antenna gated with 15 fs light pulses

Abstract: We report on the ultrabroadband coherent detection of radiation in wavelengths spanning from far to midinfrared with a low-temperature-grown GaAs photoconductive dipole antenna gated with 15 fs light pulses. The detected spectral frequency exceeds 20 THz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 9 publications
1
63
0
Order By: Relevance
“…In a few cases, however, ultrabroad bandwidths (>10 THz) have been reported. Kono et al 17 reported a THz detection up to 20 THz with a low-temperature-grown GaAs (LT-GaAs) PDA gated with 15 fs light pulse. It was quite a surprising result as the LT-GaAs they used exhibited a relatively long carrier lifetime of ∼1.4 ps.…”
Section: Broadband Thz Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a few cases, however, ultrabroad bandwidths (>10 THz) have been reported. Kono et al 17 reported a THz detection up to 20 THz with a low-temperature-grown GaAs (LT-GaAs) PDA gated with 15 fs light pulse. It was quite a surprising result as the LT-GaAs they used exhibited a relatively long carrier lifetime of ∼1.4 ps.…”
Section: Broadband Thz Generationmentioning
confidence: 99%
“…It was quite a surprising result as the LT-GaAs they used exhibited a relatively long carrier lifetime of ∼1.4 ps. According to the authors, the fast response of the PDA was explained by the fast rise in the photocurrent upon excitation by the ultrashort laser pulse, 17 and the physical origin of the fast photocurrent within ∼100 fs might be explained by the ballistic transport of the photoexcited electrons in the biased electric field. 18 In this picture, the PDA works as an integration detector, so the photocurrent from the antenna should be proportional to the time integration of the incident THz radiation.…”
Section: Broadband Thz Generationmentioning
confidence: 99%
“…Phase data can in principle reveal details of the starting mechanism of the hybrid oscillations, but they are technically difficult to obtain due to dispersion and absorption effects in the semiconductor (Leitenstorfer et al,. 1999, Kono et al, 2000. Ignoring this phase information, Hasselbeck et al (Hasselbeck et al, 2002) used a broadband interferometric method with two 30 fs pump pulses directed at nearby regions in InAs to extract transient THz radiation signals interfering in the far field.…”
Section: Femtosecond-scale Optics 154mentioning
confidence: 99%
“…All parabolic mirrors used had diameter of 5 cm. The receiver was again fabricated on "low temperature grown" GaAs, 8 this time using bow tie electrodes with length of 100 m and width of 27 m. The current induced by the terahertz radiation was initially preamplified before detection using lock-in techniques, referenced to a 1 kHz mechanical chopper placed in the pump arm, so that the electric field of the terahertz pulse could be measured. Terahertz pulses with signal to noise ratio of approximately 1200:1 were routinely obtained using this system, which could be enclosed in a dry box to allow measurements to be made in a purged nitrogen atmosphere if required.…”
Section: B Reflection By Slabsmentioning
confidence: 99%